Kontribusi Daya Ledak Otot Lengan Dan Kelenturan Terhadap Ketepatan Service Slice Tenis Atlet Pelatihan Tenis Lapangan (Ptl) Universitas Negeri Padang - Azizil Fikri (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2021)
This study aims to determine how big the contribution of arm muscle explosive power and waist flexibility to the accuracy of slice services for PTL UNP athletes. This research is a Classroom Action Research (CAR) with a sample of 20 people. These classroom action research steps include the preparation stage, diagnostics, and classroom action plan to solve problems. The procedures for this class action research are planning, implementing the action, observing, and reflecting in each cycle. This research uses an instrument. From the results obtained, flexibility contributes significantly to the accuracy of service of PTL tennis athletes at Padang State University, which is indicated by the results obtained, namely r count 0.47 > r table 0.444, and a contribution of 22.09% is obtained. In conclusion, there is a jointly significant contribution between arm muscle explosive power and flexibility to the accuracy of the services of PTL tennis athletes, Padang State University; the results indicate this obtained R count 0.54> R table 0.444, as well as the contribution of the two independent variables ( ) to the variable (Y) of 29.16% Keywords: Arm Muscle Explosiveness, Flexibility, Tennis Service Slice Accuracy